Introducing the moon to South African natural science classrooms - Kelfkens, Lesley (My University, 2009)
This dissertation concerns the the problem that natural science teachers with limited astronomy backgrounds have to teach new curriculum content about lunar motion, phases and eclipses. My study aims to establish: 60 teachers’ knowledge of lunar phenomena through surveys; whether an intervention incorporating models and activities is effective at improving a case study group’s understandings; how the case study teachers use these activities and models in the classroom. My results indicate that the majority of natural science teachers have little formal astronomy education. Only two teachers held a scientific understanding of lunar phenomena. The intervention led towards a more scientific understanding amongst the case study group. Scale is essential for developing an understanding of lunar phenomena and models are extremely beneficial, but participants experience spatial problems when viewing models from an external perspective. I propose in-service training in small groups for building knowledge and increasing confidence for teaching this content.
Keywords: Astronomy; curriculum; Moon; phases; eclipses; models; scale